2019
DOI: 10.1108/jkm-03-2019-0129
|View full text |Cite
|
Sign up to set email alerts
|

The performance implications of knowledge management and strategic alignment of MNC subsidiaries

Abstract: Purpose The purpose of this paper was to investigate antecedents and results of strategic choices of multinational corporation (MNC) subsidiaries in Croatia economy. Hence, the authors examined knowledge management and its association with performance. Additionally, they explored which of the strategies will be most likely chosen by subsidiaries in transitional economies that are characterized by market volatility and uncertainty. Design/methodology/approach Data were collected from a survey of 131 MNC subsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 149 publications
(220 reference statements)
1
23
0
Order By: Relevance
“…Firstly, the authors controlled for firm size using the logarithm of a number of employees (Biscotti et al , 2018) on the basis of research suggesting that smaller firms, despite having less resources, and therefore, a reduced capacity to generate knowledge, might be able to apply knowledge more quickly due to a lack of bureaucracy (Dabic and Kiessling, 2019). Next, we controlled for industry category (Segarra-Ciprés and Bou-Llusar, 2018), on the basis that businesses in different industries may show different organizational characteristics (Wiklund and Shepherd, 2005) and reflecting the empirical evidence showing that industry sector affects KM (Meroño-Cerdan et al , 2007; Wu and Chen, 2014; Dabic and Kiessling, 2019). Accordingly, three industry groups were taken into account: the industrial and service sectors were considered the second and third control variables, respectively, with the construction sector being used as the default.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the authors controlled for firm size using the logarithm of a number of employees (Biscotti et al , 2018) on the basis of research suggesting that smaller firms, despite having less resources, and therefore, a reduced capacity to generate knowledge, might be able to apply knowledge more quickly due to a lack of bureaucracy (Dabic and Kiessling, 2019). Next, we controlled for industry category (Segarra-Ciprés and Bou-Llusar, 2018), on the basis that businesses in different industries may show different organizational characteristics (Wiklund and Shepherd, 2005) and reflecting the empirical evidence showing that industry sector affects KM (Meroño-Cerdan et al , 2007; Wu and Chen, 2014; Dabic and Kiessling, 2019). Accordingly, three industry groups were taken into account: the industrial and service sectors were considered the second and third control variables, respectively, with the construction sector being used as the default.…”
Section: Methodsmentioning
confidence: 99%
“…MNEs use this reverse knowledge transfer and a two-way approach to become more innovative and improve their competitiveness which helps them overcome the various liabilities associated with internationalization (Mudambi, Piscitello, & Rabbiosi, 2014;Rabbiosi & Santangelo, 2013). And, superior knowledge management capabilities ultimately help MNEs improve their performance (Dabic & Kiessling, 2019). For instance, studies by Peng, Qin, Chen, Cannice and Yang (2017) and Zhang and Edwards (2007) on subsidiaries of Chinese MNEs in the United States has shown that reverse knowledge transfer not only leads to the diffusion of best practices but also allowed the HQ to enhance its strategic asset seeking motivations.…”
Section: Discussionmentioning
confidence: 99%
“…The process of knowledge transfer could be by a strategy of replication or imitation (Hoopes and Madsen, 2008), which depends on the subsidiary's effort to become a knowledge provider acknowledged by the recipient headquarters (Frost et al, 2002). Therefore, the subsidiary needs an organizational design that favors the transfer (Joia and Lemos, 2010) and the alignment (Dabic and Kiessling, 2019) of knowledge between the subsidiary and the headquarters. Organizational innovation (Birkinshaw et al, 2008;Garcı ´a-Morales et al, 2012) allows the organizational design adaptation, which allows structural alignment for knowledge transfer.…”
Section: Literature Reviewmentioning
confidence: 99%